2021
DOI: 10.1002/hbm.25354
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copy number variations on brain structure and risk for psychiatric illness: Large‐scale studies from theENIGMAworking groups onCNVs

Abstract: The Enhancing NeuroImaging Genetics through Meta-Analysis copy number variant (ENIGMA-CNV) and 22q11.2 Deletion Syndrome Working Groups (22q-ENIGMA WGs) were created to gain insight into the involvement of genetic factors in human brain development and related cognitive, psychiatric and behavioral manifestations.To that end, the ENIGMA-CNV WG has collated CNV and magnetic resonance imaging (MRI) data from 49,000 individuals across 38 global research sites, yielding one of the largest studies to date on the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 183 publications
3
29
0
Order By: Relevance
“…For example, the study conducted by the Schizophrenia Working Group identified more than 100 independent loci associated with schizophrenia [38], suggesting that these variants contribute to the genetic susceptibility for primary psychosis [13]. Simultaneously, the detection of chromosomal rearrangements pointed out the implication of copy number variants-CNVs, small insertions and deletions (indels), as for the 22q11.2 microdeletion syndrome [31,[39][40][41]. Compared to single CNVs and indels, a smaller contribution to the risk of developing primary psychosis was found for each single nucleotide variation-SNV [17,19,39].…”
Section: Sociodemographic Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the study conducted by the Schizophrenia Working Group identified more than 100 independent loci associated with schizophrenia [38], suggesting that these variants contribute to the genetic susceptibility for primary psychosis [13]. Simultaneously, the detection of chromosomal rearrangements pointed out the implication of copy number variants-CNVs, small insertions and deletions (indels), as for the 22q11.2 microdeletion syndrome [31,[39][40][41]. Compared to single CNVs and indels, a smaller contribution to the risk of developing primary psychosis was found for each single nucleotide variation-SNV [17,19,39].…”
Section: Sociodemographic Risk Factorsmentioning
confidence: 99%
“…CNVs and indels are unique and rare in the general population. Instead, common in individuals with neurodevelopment disorders, including primary psychosis [17,40]. In fact, approximately 2.5% of schizophrenia cases have a known CNV [40], suggesting that these specific genetic variants might take part in the pathogenesis of primary psychosis.…”
Section: Sociodemographic Risk Factorsmentioning
confidence: 99%
“…A previous study found delta frequency (<4 Hz) EEG activity to be reduced in ADHD patients not using psychostimulant medication ( Furrer et al, 2017 ) the authors related their finding to reduced cortical grey matter, and delays in its maturation in ADHD ( Nakao et al, 2011 ; Shaw et al, 2006 ; Shaw et al, 2010 ). In contrast, imaging studies have suggested increased cortical grey matter thickness in 22q11.2DS, alongside changes in corticothalamic networks ( Lin et al, 2017 ; Sønderby et al, 2022 ; Sun et al, 2020 ), which may reduce across adolescence ( Schaer et al, 2009 ). This could therefore explain our finding of increased SW amplitude in 22q11.2DS, and its relationship with ADHD symptoms, as it has been previously demonstrated (in adults) that greater SW amplitude is associated with greater cortical thickness ( Dubé et al, 2015 ).…”
Section: Discussionmentioning
confidence: 94%
“…CNVs at proximal 16p11.2 are also associated with neurodevelopmental disorder, intellectual disability, attention-deficit hyperactivity disorder, depression, and autism [ 34 , 36 , 47 , 48 , 49 , 50 , 51 ]. Finally, CNVs at 22q11.2 are associated with congenital heart disease, neurodevelopmental disorders, intellectual disability, autism spectrum disorders, and other neuropsychiatric conditions [ 7 , 48 , 52 , 53 ]. Together, these data indicate that clinical manifestations of CNVs at the eight loci in this study are not limited to schizophrenia; they have pleiotropic clinical effects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, to study pathophysiology and neuropsychiatric manifestations of the rare pathogenic CNVs associated with psychiatric disorders, two working groups were formed by the Enhancing NeuroImaging Genetics through Meta-Analysis (ENIGMA) consortium formed: the ENIGMA 22q11.2 Deletion Syndrome Working Group (22q-ENIGMA WG) and the ENIGMA-CNV Working Group (ENIGMA-CNV WG) [ 7 ]. These two working groups have reported the effects of several rare pathogenic CNVs, including 22q11.2 [ 7 ], 16p11.2 distal [ 8 ], 15q11.2 [ 9 ], and 1q21.2 [ 10 ], on brain structure, cognition, and neuropsychiatric symptoms, which has increased our understanding of the genetic etiology and neurobiology of schizophrenia and related psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%